Determinants of Implementation of Special Group Reservation Scheme by Procuring Entities - Melissa Michael Ngomuo; Godfrey Isaac Mwandosya (Journal of International Trade, Logistics and Law, 2023)
This paper aims to assess the determinants of the implementation of special group reservation schemes by procuring entities. The study used a mixed-methods approach, using both quantitative and qualitative methods. Qualitative information was gathered using techniques including interviews for the descriptive nature of the study, and quantitative data was gathered by questionnaire. Data was analyzed by both qualitative and quantitative techniques. Based on the analysis, the descriptive statistic shows that the majority of the respondents agreed with the statements that financial capacity, vendor quality index, and technical capacity play a great role in the special group reservation scheme in terms of increasing the number of contracts awarded to special groups, increasing value of contracts awarded to special groups, and increasing the percentage of special groups beneficiaries since the value of the mean scores is above the 3.63. These results imply that the capacity of special groups is one of the determinant factors influencing the implementation of special groups in public entities. Also, the capacity of the special group was found to have a positive influence on the implementation of the special group reservation scheme in public entities. About the significance of the variable, the findings show the value of the capacity of the special group in the implementation of a special group reservation scheme. The study recommends that the government should ensure sufficient allocation of financial resources, adequacy of equipment and technical competence, adequate physical facilities, high managerial capability, experience, and personnel to achieve a high level of implementation of the special group reservation scheme.